The Development of Focusky as Learning Media on Recount Text to Improve Students' Vocabulary Mastery - Natra, Bima; Pahmi, Pahmi; Syahfutra, Wandi (Journal of Educational Sciences, 2024)
This study delves into the development and implementation of an application-based learning media called "Verbiloquy" aimed to improve students' English vocabulary mastery. The research was conducted at SMK Negeri 4 Pekanbaru with 32 students from class X DPK-BT 2. The ADDIE methodology, which includes Analysis, Design, Development, Implementation, and Evaluation, provided a systematic approach to develop and implement the learning media product. Data collection involved pre-test and post-test assessments to measure the impact of the learning media on students' vocabulary mastery. Material and media experts evaluated the developed product, with results indicating high feasibility and effectiveness. The result of students’ vocabulary test was improved in the quality of their vocabulary ability measured by the result of the N-gain classification showed at 0.54 increase in students' vocabulary test scores, categorizing the improvement as "Medium." Comparison with previous studies revealed similar positive outcomes in terms of improving English vocabulary mastery using different learning tools. The study concludes that "Verbiloquy" is an effective tool for enhancing students' vocabulary skills, contributing to a more engaging and efficient learning experience. The researcher highlights the potential of Focusky as a valuable learning media in improving students' language proficiency.